The Management of Oral Anticoagulant Therapy: The Patient’s Point of View - Barcellona, Doris; Contu, Paolo; Sorano, Gian Gabriele; Pengo, Vittorio; Marongiu, Francesco (Thrombosis and Haemostasis, 2000)
The aims of this study were to investigate on the general adhesion of the patients to oral anticoagulant therapy, and particularly on the quality of life of our patients, the doctor-patient relationship and the Centre-patient relationship. For this purpose we administered a questionnaire containing 17 main questions each with a maximum of 4 secondary questions. The questionnaire was administered to two groups of 127 and 137 oral anticoagulated patients (127 males and 137 females, mean age 55 ± 19 years), followed at two Anticoagulation Clinics, in two Italian cities, Cagliari (Sardinia) and Padua (North East Italy). The cities differed in the number of patients monitored and the management modalities of anticoagulation. The results show that oral anticoagulant therapy does not limit the life-style of the patients. Only 11% of the patients complain of limitations to their daily life. Fifty-two percent believe their health has improved, and 87% are not afraid of negative consequences. The doctor-patient relationship is considered very important by 96% of patients. Seventy-eight percent refer to the Anticoagulation Clinic also for other health problems, 93% consider it important to be assessed by the doctor at the Anticoagulation Clinic, while 83% believe the doctor should always hand out the results personally. We conclude that in general oral anticoagulant therapy is accepted by the majority of patients, in spite of the need for periodic monitoring. The doctor-patient relationship should be taken into account, even in the case of a monitored, computer-assisted method of dose-adjustment.
Keywords: Oral anticoagulants; quality of life; anticoagulation clinic